EFFECT OF FREQUENCY OF FEEDING ON GROWTH AND SURVIVAL RATE OF Hemibagrus nemurus IN MAINTENANCE WITH BIOFLOC SYSTEM - Lestari Dwi Ayu Safitri; Iskandar Putra; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted in February until March 2019 at Aquaculture Technology Laboratory of Fisheries and Marine, University Riau. The purpose of this study was to determine the effect of feeding on the growth and survival rate of Hemibagrus nemurus on maintenance with biofloc system. The method used is an experimental method with a completely randomized complete design (CRD) with four levels of treatment, namely P1 (1 time a day feeding at 6 a.m.), P2 (2 times a day feeding (6 a.m. and 6 p.m ) P3 (3 feeding times at 6 a.m., 12 a.m. and 6 p.m.) and P4 (4 times a day feeding at 6 a.m., 10 p.m., 12 a.m. and 6 p.m.). The results showed that the frequency of different feedings had an effect on the growth and survival rate of Hemibagrus nemurus on maintenance media with a biofloc system. The best treatment is P4 (4 times a day feeding at 6 a.am., 10 a.am., 12 a.m. and 6 p.m.), with absolute growth weight of 5.10 g, absolute length of 2.28 cm, specific growth rate of 2.25%, feed efficiency 92.76% and 100% survival rate. Water quality during the study was pH 6.67-6.84, temperature 27.55 - 28.18 °C, DO 5.18 - 5.83 mg / l and ammonia 0.002-0.007 mg / l. Keywords: Frequency, Hemibagrus nemurus, growth, survival rate, bioflok